A European civil society elite? Analysing capital and drama at the European Economic and Social Committee. Issue 1 (1st January 2023) - Uhlin, Anders; Arvidson, Malin
ABSTRACT: Contributing to research on civil society elites in the EU context, this article focuses on the European Economic and Social Committee (EESC). It explores who the main actors are, what roles they play, and what resources they use, value, and compete for in this arena. The theoretical starting points are grounded in Bourdieu's notions of field and capital and a Goffmanesque approach to drama. Based on semi-structured interviews with EESC members and administrators, observations at EESC meetings, and document analysis, the study explores the types of capital linked to different actors and roles, stages, and scripts in the EESC field. The most valued capital across EESC stages are social capital in the form of personal networks, and cultural capital in the form of negotiation skills and issue-specific knowledge. Actors are supposed to follow a script of being pro-European, representing organised civil society in Europe, and aiming at consensus. Being active at the EESC stages, at least in leading roles, gives actors a kind of EESC-specific capital in the form of access to influential EU decision-makers.